Arterial hypoxaemia in cirrhosis: fact or fiction?. Issue 6 (1st June 1998) - Møller, S; Hillingsø, J; Christensen, E; Henriksen, J H
Abstract : Background —Although low arterial oxygen tension (Po 2 ) has been claimed to occur in one to two thirds of patients with cirrhosis, hypoxaemia appears to be rare in clinical practice. Aims —To assess the frequency of arterial hypoxaemia in cirrhosis in relation to clinical and haemodynamic characteristics. Patients —One hundred and forty two patients with cirrhosis without significant hepatic encephalopathy (grades 0–I) (41 patients in Child class A, 57 in class B, and 44 in class C) and 21 patients with hepatic encephalopathy. Results —Mean Po 2 in kPa was 11.3 in Child class A, 10.8 in class B, 10.6 in class C, and 10.6 in patients with encephalopathy (p<0.05). The fraction of patients with Po 2 below the lower normal limit of 9.6 kPa was 10%, 28%, 25%, and 43%, respectively in class A, B, C, and in patients with encephalopathy (p<0.05). Oxygen saturation (So 2 ) in these groups was respectively: 96%, 96%, 96%, and 93% (NS). So 2 was below the lower limit of 92% in 0%, 9%, 7%, and 24% (p<0.05). In patients without hepatic encephalopathy, a multivariate regression analysis revealed that independent determinants of a low Po 2 were a high arterial carbon dioxide tension, a low systemic vascular resistance, and a low indocyanine green clearance (p<0.0001). Conclusion —The prevalence of arterial hypoxaemia in cirrhosis is about 22% in patients without encephalopathy, but it varies from 10–40% depending on the degree of hepatic dysfunction. Arterial hypoxaemia in patients with cirrhosis of differing severity seems lower than previously reported, and patients with severe arterial hypoxaemia are rare.